KRITIK TERHADAP NILAI PHALLOSENTRIS DALAM NOVEL SAMAN, LARUNG, DAN ANIME JUNJOU ROMANTICA: STUDI KOMPARATIF GENRE ‘SASTRA WANGI’ AND GENRE ‘YAOI’ - Wawat Rahwati (Universitas 17 Agustus 1945 Surabaya, 2017)
Abstract. This paper discuss about gender and sexuality in popular literature by doing comparative studies of Indonesian literary works and Japanese literary works. In Indonesian literature, there is a genre called ‘sastra wangi’ (fragrant literature) that has emerged since Ayu Utami’s first novel Saman published in 1998 two weeks prior to Suharto’s fall, and in 2001 Ayu Utami’s next Larung was published. Those two novels represent the ‘sastra wangi’ genre. The label of ‘sastra wangi’ refers to somewhat disapproving term, because for the writer like Ayu Utami the freedom of expression is everyone’s right, including the discussing about sexuality. Meanwhile in Japanese literature and populer culture, there is a genre called ‘yaoi’ which illustrating a homesexual relation between male. ‘yaoi’ genre can be found at many artworks, such as manga, anime, novel, and film. The anime Junjou Romantica is one of the artwork represented the ‘yaoi’ genre. This paper is aim at showing how discourse in novel Saman, Larung, and anime Junjou Romantica are represented through the narration and character’s expression, are those the discourses express the ‘woman freedom’, and then are there any parallelism between ‘sastra wangi’ genre and ‘yaoi’ genre. By using comparative method with postructuralism feminist (postfeminism) perspective, it is found those novels Saman, Larung, and anime Junjou Romantica showing many discourses through portraying the character’s expression and thier narration. The discourses in novel Saman and Larung are conveying the criticism of phallocentris’values, such as denying a marriage's value and destabilizing heterosexual relation by doing free sex and homosexual attitude. From all the main character which portrayed in novel Saman, Larung, and Junjou Romantica, we can see the same discourses reveal the expression of woman freedom from male’s domination. Keyword: Yaoi genre, Fragrant literature, Junjou Romantica, Postfeminism